The Role of Prosecution Related to Prosecutor's Demand in Enforcing the Criminal Action of Narcotics - Septian Nanang Pangestu; Lathifah Hanim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
The objectives of this research are: to analyze prosecutors related to prosecutors 'demands in enforcing the narcotics crime law. To analyze the obstacles and solutions faced in making prosecutors' demands in enforcing the narcotics crime law.The method used by researchers isjuridical sociological approach to law and the specification in this research is including analytical descriptive. Based on the results of the research that the role of the prosecutor related to prosecutors' demands in enforcing the narcotics crime law has been fulfilled. The elements of a criminal act violating Article 127 paragraph (1) letter a of Act No. 35 of 2009 concerning Narcotics and it was proven to be against the law because the defendant had the intention to use methamphetamine himself or his own interests, while drugs can only be used for the benefit of developing science and technology. The obstacle is that witnesses who are majority members of the police, when called to be witnesses at trial, often do not attend the trial because they are busy with their superiors, which makes the prosecution process take a long time. The modus operandi in narcotics convictions is because the perpetrators work very well. To overcome the obstacles prosecutors carry out an activity, one of which is holding knowledge sharing meetings between law enforcers and related agencies, to gain unity in perceptions in handling Narcotics crime cases. Then carry out management improvements, so as to minimize the opportunity for narcotics crime to occur. Starting from the practice of handling narcotics crime, the first origin of narcotics crime is from one of the weaknesses of management.